Design of Cell Construction for Immunosensor Based Quartz Crystal Microbalance (QCM) - Farida Wahyuni; Setyawan Purnomo Sakti; Unggul P. Juswono; Fenny Irawati; Nur Chabibah (Natural B, Journal of Health and Environmental Sciences, 2012)
The biosensor is a sensor device that combines biological compounds with a transducer. One type of biosensor that uses mass change detection techniques are QCM (Quartz Crystal Microbalance). QCM is a sensor that works with the principle of quartz crystal frequency shift due to mass deposition on the surface of the crystal. QCM can be used to detect the reaction between the molecules, so that the QCM can serve as biosensors that can be used for the diagnosis of a disease. In the development of QCM immunosensor for there are many problems, one of which is the construction of the cell. Construction cells can be used as a reaction between biomolecules. Construction of cells made of white Teflon. To keep QCM sensors are not experiencing physical stress that can lead to rupture due to pressure from the Teflon o-ring is used as an insulating silicon. The results of this study indicate that the construction of the cells created can be used as a medium for immobilization of Bovine Serum Albumin observations (BSA) on the surface of the sensor.